HAK PEKERJA YANG TERKENA PHK SEBELUM MASA KONTRAK BERAKHIR - Asri Wijayanti; Kaharudin Putra Samudra (JURNAL ILMIAH LIVING LAW, 2021)
The work agreement for a specific time should end after the contract period is over. The fact is that in the community. It is often found that the contract period ends before the time specified in the work agreement for a certain time. The purpose of this research determined the rights of workers who were terminated before the contract period ended and their legal remedies. This research was normative juridical by using a statute approach to the Supreme Court decision number 16 K/Pdt.Sus-PHI/2020. The first result of this research that workers should receive rights in the form of wages for the remainder of the contract period when their employment relationship was terminated unilaterally by the employer before the contract period ends in accordance with Article 62 of Manpower Law. The workers can do it because this decision had been in kracht van gewijsde since the decision was read by the judge of the Supreme Court and there was no legal action for review. The conclusion should be the decision of the Supreme Court grant the right of the remaining contract period in accordance with Article 62 of Manpower Law.